Anionic Bipyridyl Ligands for Applications in Metallasupramolecular Chemistry. Issue 19 (2nd April 2014) - Pascu, Mirela; Marmier, Mathieu; Schouwey, Clément; Scopelliti, Rosario; Holstein, Julian J.; Bricogne, Gérard; Severin, Kay
Abstract The facile synthesis of anionic bipyridyl ligands with dinuclear clathrochelate cores is described. These metalloligands can be obtained in high yields by the reactions of M(ClO4)2(H2O)6 (M: Zn, Mn, or Co) with 4‐pyridylboronic acid and 2, 6‐diformyl‐4‐methylphenol oxime or 2, 6‐diformyl‐4‐tert‐butylphenol oxime, followed by deprotonation. The ligands are interesting building blocks for metallasupramolecular chemistry, as evidenced by the formation of a Pt‐based molecular square and four coordination polymers with 2D or 3D network structures. Competition experiments reveal that the utilization of anionic bipyridyl ligands can result in significantly more stable assemblies.